The Concept of Education in the Qur'an, Surah Al-Alaq, and its Relevance to Contemporary Education - Fatimatul Asroriah; Ndaru Putri Yudhiarti; Imam Shodiq Anshori (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2023)
The article discusses the concept of education found in the Qur'an, specifically in Surah Al-Alaq, and its relevance to the contemporary education context. Surah Al-Alaq is one of the early chapters revealed to Prophet Muhammad SAW, emphasizing the importance of knowledge and learning in Islamic teachings. By analyzing key verses in Surah Al-Alaq, we can understand the fundamental principles of education emphasized in Islam. Surah Al-Alaq begins with the words